2012
DOI: 10.1002/prot.24108
|View full text |Cite
|
Sign up to set email alerts
|

Coarse grain lipid–protein molecular interactions and diffusion with MsbA flippase

Abstract: Coarse-grained (CG) modeling has proven effective for simulating lipid bilayer dynamics on scales of biological interest. Modeling the dynamics of flexible membrane proteins within the bilayer, on the other hand, poses a considerable challenge due to the complexity of the folding or conformational landscape. In the present work, the multiscale coarse-graining method is applied to atomistic peptide-lipid "soup" simulations to develop a general set of CG protein-lipid interaction potentials. The reduced model wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 75 publications
(112 reference statements)
0
33
0
Order By: Relevance
“…The sidechain‐centric model of Hills et al is used to represent protein–protein interactions, which maintains a similar mapping of heavy atoms to CG sites. Tabulated lipid–protein protein interactions were developed previously using MS‐CG . Transmembrane peptide is weakly biased to α‐helical structure by assigning harmonic springs ( K = 150 kJ mol −1 nm −2 ) between α‐carbons pairs within 10.5 Å separated by two or more bonds.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sidechain‐centric model of Hills et al is used to represent protein–protein interactions, which maintains a similar mapping of heavy atoms to CG sites. Tabulated lipid–protein protein interactions were developed previously using MS‐CG . Transmembrane peptide is weakly biased to α‐helical structure by assigning harmonic springs ( K = 150 kJ mol −1 nm −2 ) between α‐carbons pairs within 10.5 Å separated by two or more bonds.…”
Section: Methodsmentioning
confidence: 99%
“…To explore the phase properties of various CG bilayers, simulations are conducted at constant surface tension to determine the equilibrated area per lipid. Minimal changes are made to the model scheme so that protein‐lipid potentials previously developed by Ward et al remain compatible for simulations of membrane proteins . Stable CG bilayer simulations of realistic geometry are demonstrated for membranes containing DOPC, DOPE, 1‐palmitoyl‐2‐oleoyl‐phosphatidyl‐choline (POPC), 1‐palmitoyl‐2‐oleoyl‐phosphatidyl‐ethanolamine (POPE), phosphatidylglycerol (POPG), cholesterol (Chol), and cardiolipin (CL).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, current models for ABC-type translocases propose an alternating opening of lateral entry and exit pathways for the transported phospholipid substrate to the central cavity formed by the transmembrane helices. Coarse-grained modelling has revealed lipid binding to the ABC transporter MsbA within the grooves formed between transmembrane helices [193]. Similarly, scramblases appear to display such potential grooves.…”
Section: General Mechanisms Of Handling Lipids By Lipid Transportersmentioning
confidence: 99%
“…A large range of conformations were accessible at room temperature, in line with the observation of a more closed and dynamic state of the nucleotide free MsbA measured using EPR. The behavior of lipid surrounding MsbA in three conformations [74] showed that a ring of annular lipid formed, which was not homogeneous. Distortions of the membrane bilayer structure were observed and also lipid molecules reaching into the substrate binding site.…”
Section: Computational Investigation Of the Conformations And Dynamicmentioning
confidence: 97%